Polymer film and use thereof
By controlling the product of melt index and thickness ratio of each layer in the polymer film, the problem that the prior art is difficult to meet safety, optical performance and acoustic isolation performance at the same time is solved, and the high-performance acoustic isolation and optical performance of the polymer film are achieved.
Patent Information
- Application Number
- JP2024052664
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-19
- Filing Date
- 2024-03-28
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-03-28
AI Technical Summary
Existing multilayer polymer films are difficult to meet safety, optical properties and acoustic isolation properties simultaneously.
By controlling the product of the melt index and thickness ratio of each layer, the product of the first and second partial layers is ensured to be within a specific range, thereby optimizing the structural consistency of the polymer film.
It achieves excellent performance of polymer films in the preparation of acoustic isolation, optical properties and safety (mechanical strength), and is suitable for the preparation of high-performance acoustic isolation glass.
Smart Images

Figure 2025044113000001 
Figure 2025044113000002 
Figure 2025044113000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer film, specifically to a multilayer polymer film characterized by a product of melt index (MI) and thickness ratio, and also to a laminated glass produced using the polymer film. [Background technology]
[0002] Laminated glass is a composite glass material made by sandwiching a polymer film between two glass sheets and bonding the glass sheets and the polymer film together using a heat press. Laminated glass is widely used in the automotive and construction industries due to its excellent impact resistance and safety.
[0003] By using a multi-layered polymer film as an interlayer of laminated glass, the sound insulation function of the laminated glass can be improved. The above polymer film has two outer layers and one inner layer disposed between the two outer layers, and achieves sound insulation function by increasing the thickness of the inner layer and adjusting the viscoelastic properties of the inner layer to increase the attenuation of sound vibration. However, none of the conventional laminated glasses could simultaneously satisfy safety, optical properties, and sound insulation performance. Summary of the Invention [Means for solving the problem]
[0004] In view of the above, the present invention relates to a polymer film consisting of a first part and a second part. According to this study, by controlling the melt index of each layer of the first part and the second part, and the product of the melt index and the thickness ratio of each layer of the first part and the second part, it is possible to impart good structural uniformity to the polymer film, and it has been found that the laminated glass provided using this polymer film has excellent sound insulation effect, excellent optical properties, and excellent safety (high mechanical strength). Therefore, the polymer film of the present invention is particularly suitable for producing sound-insulating laminated glass.
[0005] It is therefore an object of the present invention to provide a polymeric film comprising a first portion and a second portion laminated to the first portion, the first portion and the second portion independently comprising one or more layers. wherein each layer of the first portion independently has a melt index in the range of 3.5 g / 10 min to 10.0 g / 10 min, and each layer of the second portion independently has a melt index less than 3.5 g / 10 min; each layer of the first portion independently has a thickness ratio of its thickness to a total thickness of the first portion and the second portion, and a product of its melt index and the thickness ratio, wherein the sum of the products of each layer of the first portion is in the range of 0.39 g / 10 min to 2.50 g / 10 min; Further, each layer of the second portion independently has a thickness ratio of its thickness to the total thickness of the first portion and the second portion, and a product of its melt index and the thickness ratio, wherein the sum of the products of each layer of the second portion is in the range of 1.10 g / 10 min to 2.95 g / 10 min.
[0006] In some embodiments of the invention, the melt index of each layer of the second portion is independently from 1.5 g / 10 min to 3.3 g / 10 min.
[0007] In some embodiments of the present invention, the melt index of each layer of the first portion and the melt index of each layer of the second portion are measured according to ASTM D1238 at 190° C. and a load of 2.16 kg.
[0008] In some embodiments of the invention, each layer of the first portion and each layer of the second portion independently comprises a polyvinyl acetal, which may be selected from the group consisting of poly(vinyl formal), poly(vinyl acetal), poly(vinyl butyral), poly(vinyl pentanal), poly(vinyl hexanal), and combinations thereof. In a preferred embodiment of the invention, each layer of the first portion and each layer of the second portion independently comprises poly(vinyl butyral).
[0009] In some embodiments of the present invention, each layer of the first part independently comprises a polyvinyl acetal having the following properties: a degree of acetalization of 56 mol% to 74 mol%, a degree of acetylation of 5 mol% to 15 mol%, and a content of hydroxyl groups of 20 mol% to 30 mol%, based on the total number of moles of hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal contained in each layer of the first part.
[0010] In some embodiments of the present invention, each layer of the second part independently comprises a polyvinyl acetal having the following properties: a degree of acetalization of 60 mol% to 75 mol%, a degree of acetylation of 0.1 mol% to 5 mol%, and a content of hydroxyl groups of 20 mol% to 35 mol%, based on the total number of moles of hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal contained in each layer of the second part.
[0011] In some embodiments of the present invention, the polyvinyl acetal included in each layer of the first portion independently has a number average molecular weight (Mn) in the range of 100,000 to 240,000.
[0012] In some embodiments of the present invention, the polyvinyl acetal contained in each layer of the second portion independently has a number average molecular weight (Mn) in the range of 90,000 to 120,000.
[0013] In some embodiments of the invention, each layer of the first portion and each layer of the second portion independently further comprises a plasticizer.
[0014] In some embodiments of the invention, each layer of the first portion and each layer of the second portion independently further comprises a plasticizer, wherein each layer of the first portion independently comprises a plasticizer in an amount ranging from 55 parts by weight to 85 parts by weight based on 100 parts by weight of polyvinyl acetal contained therein, and each layer of the second portion independently comprises a plasticizer in an amount ranging from 30 parts by weight to 50 parts by weight based on 100 parts by weight of polyvinyl acetal contained therein.
[0015] In some embodiments of the invention, one or more layers of the first portion constitute first subportions and one or more layers of the second portion constitute second subportions, the first subportions and the second subportions are arranged alternately, the number of first subportions is M and the number of second subportions is N, and M and N are independently positive integers.
[0016] In some embodiments of the invention, N is M+1.
[0017] Another object of the present invention is to provide a laminated glass, which comprises, in order, a first glass sheet, an intermediate film and a second glass sheet, the intermediate film being provided by the aforementioned polymer film.
[0018] In order to make the above objectives, technical features and advantages of the present invention more apparent, the present invention will be described in detail below with reference to several embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, some embodiments of the present invention will be described in detail. However, the present invention may be embodied in various embodiments and should not be limited to the embodiments set forth in the specification.
[0020] Unless otherwise specified, the terms "a", "the", and the like in the specification and claims are intended to include both the singular and the plural.
[0021] Unless otherwise specified, the terms "first", "second", and the like in the specification and claims are used merely to distinguish between exemplified elements or components without any special meaning, and are not used to indicate priority.
[0022] In this specification and claims, "Melt Index (MI)" is measured according to ASTM D1238 at 190° C. and under a load of 2.16 kg.
[0023] In this specification and claims, the unit of number average molecular weight (Mn) is "Daltons".
[0024] In this specification and claims, "thickness ratio" refers to the ratio of the thickness of a single layer to the total thickness of a polymer film.For example, if a polymer film has a 5-layer structure with a thickness of 2 mm, and the first part of the polymer film includes three layers with a thickness of 0.5 mm, and the second part includes two layers with a thickness of 0.25 mm, the thickness ratio of each layer of the first part is 0.25, and the thickness ratio of each layer of the second part is 0.125.
[0025] In this specification and claims, the sum of the products of thickness ratio and melt index means the sum of the products of thickness ratio and melt index of each layer.For example, if the first part of polymer film has three layers, the thickness ratios of the three layers are 0.1, 0.2, 0.3, and the melt indexes are 3.5g / 10min, 4g / 10min, and 4.5g / 10min, respectively, the sum of the products of each layer of the first part is (0.1×3.5)+(0.2×4)+(0.3×4.5)=2.5.
[0026] The present invention provides a polymer film that can be used to produce laminated glass having excellent sound insulation effect, excellent optical properties, and excellent safety (high mechanical strength). The polymer film of the present invention and its uses are described in detail below.
[0027] 1. Polymer film
[0028] 1.1.Characteristics of polymer films
[0029] The polymeric film of the present invention comprises a first portion and a second portion, the first portion and the second portion being independently composed of one or more layers and having the following characteristics:
[0030] Each layer of the first portion independently has a melt index in the range of 3.5 g / 10 min to 10.0 g / 10 min. For example, the melt index of each layer of the first portion may be 3.5 g / 10 min, 3.6 g / 10 min, 3.7 g / 10 min, 3.8 g / 10 min, 3.9 g / 10 min, 4.0 g / 10 min, 4.1 g / 10 min, 4.2 g / 10 min, 4.3 g / 10 min, 4.4 g / 10 min, 4.5 g / 10 min, 4.6 g / 10 min, 4.7 g / 10 min, 4.8 g / 10 min, 4.9 g / 10 min, 5.0 g / 10 min, 6.0 g / 10 min, 7.0 g / 10 min, 8.0 g / 10 min, 9.0 g / 10 min, 10.0 g / 10 min, 11.0 g / 10 min, 12.0 g / 10 min, 13.0 g / 10 min, 14.0 g / 10 min, 15.0 g / 10 min, 16.0 g / 10 min, 17.0 g / 10 min, 18.0 g / 10 min, 19.0 g / 10 min, 20.0 g / 10 min, 21.0 g / 10 min, 22.0 g / 10 min, 23.0 g / 10 min, 24.0 g / 10 min, 25.0 g / 10 min, 26.0 g / 10 min, 27.0 g / 10 min, 28.0 g / 10 min, 29.0 g / 10 min, 30.0 g / 10 min, 31.0 g / 10 min, 32.0 g / 10 min, 33.0 g / / 10 minutes, 5.1g / 10 minutes, 5.2g / 10 minutes, 5.3g / 10 minutes, 5.4g / 10 minutes, 5.5g / 10 minutes, 5.6g / 10 minutes, 5.7g / 10 minutes, 5.8g / 10 minutes, 5.9g / 10 minutes, 6.0g / 10 minutes, 6.1g / 10 minutes, 6.2g / 10 minutes, 6.3g / 10 minutes, 6.4g / 10 minutes, 6.5g / 10 minutes, 6.6g / 10 minutes, 6.7g / 10 minutes, 6.8g / 1 0 min, 6.9g / 10 min, 7.0g / 10 min, 7.1g / 10 min, 7.2g / 10 min, 7.3g / 10 min, 7.4g / 10 min, 7.5g / 10 min, 7.6g / 10 min, 7.7g / 10 min, 7.8g / 10min, 7.9g / 10min, 8.0g / 10min, 8.1g / 10min, 8.2g / 10min, 8.3g / 10min, 8.4g / 10min, 8.5g / 10min, 8.6g / 10min , 8.7g / 10min, 8.8g / 10min, 8.9g / 10min, 9.0g / 10min, 9.1g / 10min, 9.2g / 10min, 9.3g / 10min, 9.4g / 10min, 9.5g / 10min, 9.6g / 10min, 9.7g / 10min, 9.8g / 10min, 9.9g / 10min, or 10.0g / 10min, or within a range between any two values listed herein. The first portion having a predetermined melt index can attenuate sound vibrations, thereby optimizing the sound insulation effect.
[0031] Each layer of the second portion independently has a melt index less than 3.5 g / 10 min. Preferably, each layer of the second portion independently has a melt index in the range of 1.5 g / 10 min to 3.3 g / 10 min. For example, the melt index of each layer of the second portion can be 1.5 g / 10 min, 1.6 g / 10 min, 1.7 g / 10 min, 1.8 g / 10 min, 1.9 g / 10 min, 2.0 g / 10 min, 2.1 g / 10 min, 2.2 g / 10 min, 2.3 g / 10 min, 2.4 g / 10 min, 2.5 g / 10 min, 2.6 g / 10 min, 2.7 g / 10 min, 2.8 g / 10 min, 2.9 g / 10 min, 3.0 g / 10 min, 3.1 g / 10 min, 3.2 g / 10 min, 3.3 g / 10 min, or 3.4 g / 10 min, or within a range between any two values recited herein.
[0032] Each layer of the first portion independently has a thickness ratio of its thickness to the total thickness of the first portion and the second portion, and a product of its melt index and the thickness ratio (i.e., melt index x thickness ratio), the sum of the products of each layer of the first portion being in the range of 0.39 g / 10 min to 2.50 g / 10 min. For example, the sum of the products of each layer of the first portion is 0.39g / 10min, 0.40g / 10min, 0.45g / 10min, 0.50g / 10min, 0.55g / 10min, 0.60g / 10min, 0.65g / 10min, 0.70g / 10min, 0.75g / 10min, 0.80g / 10min, 0.85g / 10min, 0.90g / 10min, 0.95g / 10min, 1.00g / 10min, 1.05g / 10min, 1.10g / 10min, 1.15g / 10min, 1.20g / 10min, 1.25g / 10min, 1.30g / 10min, 1.35g / 10min, 1.40g / 10min, 1.45g / 10min , 1.50 g / 10 min, 1.55 g / 10 min, 1.60 g / 10 min, 1.65 g / 10 min, 1.70 g / 10 min, 1.75 g / 10 min, 1.80 g / 10 min, 1.85 g / 10 min, 1.90 g / 10 min, 1.95 g / 10 min, 2.00 g / 10 min, 2.05 g / 10 min, 2.10 g / 10 min, 2.15 g / 10 min, 2.20 g / 10 min, 2.25 g / 10 min, 2.30 g / 10 min, 2.35 g / 10 min, 2.40 g / 10 min, 2.45 g / 10 min, or 2.50 g / 10 min, or within a range between any two of the values recited herein.
[0033] Each layer of the second portion independently has a thickness ratio of its thickness to the total thickness of the first portion and the second portion, and a product of its melt index and the thickness ratio (i.e., melt index x thickness ratio), the sum of the products of each layer of the second portion being in the range of 1.10 g / 10 min to 2.95 g / 10 min. For example, the sum of the products of each layer of the second portion is 1.10g / 10min, 1.15g / 10min, 1.20g / 10min, 1.25g / 10min, 1.30g / 10min, 1.35g / 10min, 1.40g / 10min, 1.45g / 10min, 1.50g / 10min, 1.55g / 10min, 1.60g / 10min, 1.65g / 10min, 1.70g / 10min, 1.75g / 10min, 1.80g / 10min, 1.85g / 10min, 1.90g / 10min, 1.95g / 10min, 2.00g / 10min, 2.05g / 10min , 2.10g / 10min, 2.15g / 10min, 2.20g / 10min, 2.25g / 10min, 2.30g / 10min, 2.35g / 10min, 2.40g / 10min, 2.45g / 10min, 2.50g / 10min, 2.55g / 10min, 2.60g / 10min, 2.65g / 10min, 2.70g / 10min, 2.75g / 10min, 2.80g / 10min, 2.85g / 10min, 2.90g / 10min, or 2.95g / 10min, or within a range between any two of the values recited herein.
[0034] As a result of the research, it was found that only when the melt index of each layer of the first part and the second part is within the above-mentioned range and the sum of the products of the melt index and the thickness ratio of each layer of the first part and the second part is within the above-mentioned range, the laminated glass using the polymer film of the present invention can exhibit excellent sound insulation effect, excellent optical properties, and excellent safety (high mechanical strength).
[0035] 1.2. Polymer film structure
[0036] The polymeric films of the present invention include a first portion and a second portion, and the first portion and the second portion are independently composed of one or more layers. Alternatively, the polymeric films of the present invention consist essentially of the first portion and the second portion, or the polymeric films of the present invention consist of the first portion and the second portion.
[0037] In the polymer film of the present invention, the first part and the second part are laminated together means that the layers of the first part and the layers of the second part are laminated in any order. For example, when the first part is composed of two A layers and the second part is composed of three B layers, the lamination order can be, but is not limited to, AABBB, ABABB, ABBBA, BABAB, or BBAAB.
[0038] In some embodiments of the present invention, one or more layers of the first portion constitute a first subportion, and one or more layers of the second portion constitute a second subportion, and each of the first subportion and the second subportion can independently comprise one or more layers. The number of first subportions is M, and the number of second subportions is N, where M and N are independently positive integers, for example, integers between 1 and 5. The first subportions and the second subportions are arranged alternately. For example, when M is 2 and N is 2, the polymer film is arranged in the order of the first subportion, the second subportion, the first subportion, and the second subportion. When M is 2 and N is 3, the polymer film is arranged in the order of the second subportion, the first subportion, the second subportion, the first subportion, and the second subportion. When M is 3 and N is 2, the polymer film is arranged in the order of the first subportion, the second subportion, the first subportion, the second subportion, and the first subportion. In a preferred embodiment of the invention, N is M+1. In a more preferred embodiment of the invention, M is 1 or 2 and N is M+1.
[0039] 1.3. Components of polymer films
[0040] In the polymer film of the present invention, each layer of the first part and each layer of the second part independently contain polyvinyl acetal as an essential component, and each layer of the first part and each layer of the second part independently may further contain other optional components such as plasticizers or other common additives, if necessary. The expression "each layer of the first part and each layer of the second part independently contain polyvinyl acetal" used herein means that each layer of the first part and each layer of the second part contain polyvinyl acetal, and the polyvinyl acetal contained in each layer of the first part or the second part may be the same or different. In some embodiments of the present invention, each layer of the first part and each layer of the second part independently may contain polyvinyl acetal and a plasticizer, and the polyvinyl acetal and plasticizer contained in each layer may be the same or different. Alternatively, each layer of the first portion and each layer of the second portion may each independently consist essentially of or consist of polyvinyl acetal and a plasticizer, and the polyvinyl acetal and plasticizer contained in each layer may be the same or different.
[0041] 1.3.1. Polyvinyl acetal
[0042] Examples of polyvinyl acetals include, but are not limited to, poly(vinyl formal), poly(vinyl acetal), poly(vinyl butyral), poly(vinyl pentanal), poly(vinyl hexanal), etc. The above polyvinyl acetals can be used alone or in combination of two or more. In a preferred embodiment of the present invention, the polyvinyl acetal is poly(vinyl butyral).
[0043] 1.3.1.1. Polyvinyl acetal in the first part
[0044] In some embodiments of the present invention, the number average molecular weight (Mn) of the polyvinyl acetal contained in each layer of the first part is independently in the range of 100,000 to 240,000. For example, the Mn of the polyvinyl acetal contained in each layer of the first part is independently in the range of 100,000, 105,000, 110,000, 115,000, 120,000, 125,000, 130,000, 135,000, 140,000, 145,000, 150,000, 155,000, 160,000, 165,000, 170,000, 17 ... The number average molecular weight of a polymer may be 0,000, 175,000, 180,000, 185,000, 190,000, 195,000, 200,000, 205,000, 210,000, 215,000, 220,000, 225,000, 230,000, 235,000, or 240,000, or within a range between any two values described herein. A higher number average molecular weight of a polymer indicates a higher degree of polymerization of the polymer, and therefore a lower polymeric fluidity and a lower melt index of the polymer. A lower number average molecular weight of a polymer indicates a higher melt index of the polymer.
[0045] In some embodiments of the present invention, the content of acetal groups in the polyvinyl acetal in each layer of the first part (i.e., the degree of acetalization) can be independently in the range of 56 mol% to 74 mol% based on the total number of moles of hydroxyl groups, acetal groups, and acetyl groups in the polyvinyl acetal in each layer of the first part. For example, the acetalization degree of the polyvinyl acetal in each layer of the first part can be independently in the range of 56 mol%, 56.5 mol%, 57 mol%, 57.5 mol%, 58 mol%, 58.5 mol%, 59 mol%, 59.5 mol%, 60 mol%, 60.5 mol%, 61 mol%, 61.5 mol%, 62 mol%, 62.5 mol%, 63 mol%, 64 mol%, 65 mol%, 66 mol%, 67 mol%, 68 mol%, 69 mol%, 70 mol%, 71 mol%, 72 mol%, 73 mol%, 74 mol%, 75 mol%, 76 mol%, 77 mol%, 78 mol%, 79 mol%, 80 mol%, 81 mol%, 82 mol%, 83 mol%, 84 mol%, 85 mol%, 86 mol%, 87 mol%, 88 mol%, 89 mol%, 90 mol%, 91 mol%, 92 mol%, 93 mol%, 94 mol%, 95 mol%, 96 mol%, 97 mol%, 98 mol%, 99 mol%, 98 mol%, 99 mol%, 99 mol%, 100 mol%, 100 mol%, 100 mol%, 100 mol%, 100 mol%, 100 ol%, 63.5 mol%, 64 mol%, 64.5 mol%, 65 mol%, 65.5 mol%, 66 mol%, 66.5 mol%, 67 mol%, 67.5 mol%, 68 mol%, 68.5 mol%, 69 mol%, 69.5 mol%, 70 mol%, 70.5 mol%, 71 mol%, 71.5 mol%, 72 mol%, 72.5 mol%, 73 mol%, 73.5 mol%, or 74 mol%, or within a range between any two values described herein. In a preferred embodiment of the present invention, the acetalization degree of the polyvinyl acetal contained in each layer of the first portion can be independently in the range of 60 mol% to 71 mol%, based on the total mole number of hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal contained in each layer of the first portion.
[0046] In some embodiments of the present invention, based on the total number of moles of hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal contained in each layer of the first part, the content of acetyl groups (i.e., the degree of acetylation) of the polyvinyl acetal contained in each layer of the first part may independently be in the range of 5 mol% to 15 mol%. For example, based on the total moles of hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal contained in each layer of the first part, the acetylation degree of the polyvinyl acetal contained in each layer of the first part can be independently 5 mol%, 5.5 mol%, 6 mol%, 6.5 mol%, 7 mol%, 7.5 mol%, 8 mol%, 8.5 mol%, 9 mol%, 9.5 mol%, 10 mol%, 10.5 mol%, 11 mol%, 11.5 mol%, 12 mol%, 12.5 mol%, 13 mol%, 13.5 mol%, 14 mol%, 14.5 mol%, or 15 mol%, or within a range between any two values described herein. In a preferred embodiment of the present invention, based on the total moles of hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal contained in each layer of the first part, the acetylation degree of the polyvinyl acetal contained in each layer of the first part is independently in the range of 7 mol% to 12 mol%.
[0047] In some embodiments of the present invention, based on the total number of moles of hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal contained in each layer of the first part, the content of hydroxyl groups of the polyvinyl acetal contained in each layer of the first part may independently be in the range of 20 mol% to 30 mol%. For example, based on the total moles of hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal contained in each layer of the first portion, the hydroxyl group content of the polyvinyl acetal contained in each layer of the first portion can independently be 20 mol%, 20.5 mol%, 21 mol%, 21.5 mol%, 22 mol%, 22.5 mol%, 23 mol%, 23.5 mol%, 24 mol%, 24.5 mol%, 25 mol%, 25.5 mol%, 26 mol%, 26.5 mol%, 27 mol%, 27.5 mol%, 28 mol%, 28.5 mol%, 29 mol%, 29.5 mol%, or 30 mol%, or within a range between any two values recited herein. In a preferred embodiment of the present invention, the hydroxyl group content of the polyvinyl acetal contained in each layer of the first part is independently in the range of 22 mol% to 28 mol% based on the total molar number of the hydroxyl group, acetal group, and acetyl group of the polyvinyl acetal contained in each layer of the first part. The lower the hydroxyl group content of the polyvinyl acetal, the higher the amount of plasticizer that the polyvinyl acetal can absorb.
[0048] 1.3.1.2. Polyvinyl acetal in the second part
[0049] In some embodiments of the present invention, the number average molecular weight (Mn) of the polyvinyl acetal contained in each layer of the second part is independently in the range of 90,000 to 120,000. For example, the Mn of the polyvinyl acetal contained in each layer of the second part is independently in the range of 90,000, 91,000, 92,000, 93,000, 94,000, 95,000, 96,000, 97,000, 98,000, 99,000, 100,000, 101,000, 102,000, 103,000, 104,000, 105,000, The value may be 106,000, 107,000, 108,000, 109,000, 110,000, 111,000, 112,000, 113,000, 114,000, 115,000, 116,000, 117,000, 118,000, 119,000, or 120,000, or within a range between any two values listed herein.
[0050] In some embodiments of the present invention, the content of acetal groups in the polyvinyl acetal contained in each layer of the second part (i.e., the degree of acetalization) can be independently in the range of 60 mol% to 75 mol% based on the total number of moles of hydroxyl groups, acetal groups, and acetyl groups in the polyvinyl acetal contained in each layer of the second part. For example, based on the total moles of hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal contained in each layer of the second portion, the degree of acetalization of the polyvinyl acetal contained in each layer of the second portion can independently be 60 mol%, 60.5 mol%, 61 mol%, 61.5 mol%, 62 mol%, 62.5 mol%, 63 mol%, 63.5 mol%, 64 mol%, 64.5 mol%, 65 mol%, 65.5 mol%, 66 mol%, 66.5 mol%, 67 mol%, 67.5 mol%, 68 mol%, 68.5 mol%, 69 mol%, 69.5 mol%, 70 mol%, 70.5 mol%, 71 mol%, 71.5 mol%, 72 mol%, 72.5 mol%, 73 mol%, 73.5 mol%, 74 mol%, 74.5 mol%, or 75 mol%, or within a range between any two values recited herein. In a preferred embodiment of the present invention, the degree of acetalization of the polyvinyl acetal contained in each layer of the second part is independently in the range of 70 mol% to 72 mol% based on the total number of moles of hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal contained in each layer of the second part.
[0051] In some embodiments of the present invention, based on the total moles of the hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal composed in each layer of the second part, the content of the acetyl group of the polyvinyl acetal contained in each layer of the second part (i.e., the degree of acetylation) can be independently in the range of 0.1 mol% to 5 mol%. For example, based on the total moles of the hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal contained in each layer of the second part, the degree of acetylation of the polyvinyl acetal contained in each layer of the second part can be independently 0.1 mol%, 0.5 mol%, 1 mol%, 1.5 mol%, 2 mol%, 2.5 mol%, 3 mol%, 3.5 mol%, 4 mol%, 4.5 mol%, or 5 mol%, or within a range between any two values described herein. In a preferred embodiment of the present invention, the polyvinyl acetal contained in each layer of the second part independently has a degree of acetylation in the range of 0.5 mol % to 1.5 mol %, based on the total number of moles of hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal contained in each layer of the second part.
[0052] In some embodiments of the present invention, the content of the hydroxyl group of the polyvinyl acetal contained in each layer of the second part can be independently in the range of 20 mol% to 35 mol% based on the total number of moles of the hydroxyl group, acetal group, and acetyl group of the polyvinyl acetal contained in each layer of the second part. For example, the content of the hydroxyl group of the polyvinyl acetal constituted in each layer of the second part can be independently in the range of 20 mol%, 20.5 mol%, 21 mol%, 21.5 mol%, 22 mol%, 22.5 mol%, 23 mol%, 23.5 mol%, 24 mol%, 24.5 mol%, 2 ... The content of hydroxyl groups of the polyvinyl acetal contained in each layer of the second part may be, for example, 0.5 mol%, 26 mol%, 26.5 mol%, 27 mol%, 27.5 mol%, 28 mol%, 28.5 mol%, 29 mol%, 29.5 mol%, 30 mol%, 30.5 mol%, 31 mol%, 31.5 mol%, 32 mol%, 32.5 mol%, 33 mol%, 33.5 mol%, 34 mol%, 34.5 mol%, or 35 mol%, or may be within a range between any two values described herein. In a preferred embodiment of the present invention, the content of hydroxyl groups of the polyvinyl acetal contained in each layer of the second part is independently in the range of 27 mol% to 29 mol%, based on the total number of moles of hydroxyl groups, acetal groups, and acetyl groups of the polyvinyl acetal constituted in each layer of the second part.
[0053] Plasticizers
[0054] A plasticizer, as used herein, is also called a plasticizer, and is a chemical substance that can modify the plasticity of a thermoplastic resin. In general, the more the amount of plasticizer added, the higher the melt index of the polymer film. The type of plasticizer is not particularly limited, and the plasticizers contained in each layer of the first part and each layer of the second part may be the same or different. Examples of plasticizers include triethylene glycol bis(2-ethylhexanoate), tetraethylene glycol bis(2-ethylhexanoate), triethylene glycol bis(2-ethylbutyrate), tetraethylene glycol bis(2-ethylbutyrate), triethylene glycol diheptanoate, tetraethylene glycol diheptanoate, dihexyl adipate, dioctyl adipate, hexylcyclohexyl adipate, diisononyl adipate, heptylnonyl adipate, dibutyl sebacate, bis[2-(2-butanoyl)-1,3-diphenyl ether] ... Examples of suitable plasticizers include, but are not limited to, esters of polybasic acids or polyhydric alcohols such as bis(2-ethylhexyl)(oxyethoxy)ethyl)adipate, polymeric adipate, dipropylene glycol dibenzoate, tripropylene glycol dibenzoate, polypropylene glycol dibenzoate, isodecyl benzoate, 2-ethylhexyl benzoate, propylene glycol dibenzoate, diisononyl phthalate, dibutoxyethyl terephthalate, castor oil, methyl ricinoleate, soybean oil, epoxidized soybean oil, and combinations thereof. In the accompanying examples, triethylene glycol bis(2-ethylhexanoate) is used as the plasticizer.
[0055] In some embodiments of the invention, each layer of the first portion independently comprises a plasticizer in an amount ranging from 55 parts by weight to 85 parts by weight based on 100 parts by weight of polyvinyl acetal contained therein. For example, based on 100 parts by weight of polyvinyl acetal in each layer of the first portion, the amount of plasticizer in each layer of the first portion can be 55 parts by weight, 56 parts by weight, 57 parts by weight, 58 parts by weight, 59 parts by weight, 60 parts by weight, 61 parts by weight, 62 parts by weight, 63 parts by weight, 64 parts by weight, 65 parts by weight, 66 parts by weight, 67 parts by weight, 68 parts by weight, 69 parts by weight, 70 parts by weight, 71 parts by weight, 72 parts by weight, 73 parts by weight, 74 parts by weight, 75 parts by weight, 76 parts by weight, 77 parts by weight, 78 parts by weight, 79 parts by weight, 80 parts by weight, 81 parts by weight, 82 parts by weight, 83 parts by weight, 84 parts by weight, or 85 parts by weight, or within a range between any two of the values recited herein. In a preferred embodiment of the invention, each layer of the first portion independently contains a plasticizer in an amount ranging from 60 parts by weight to 80 parts by weight based on 100 parts by weight of the polyvinyl acetal contained therein.
[0056] In some embodiments of the present invention, each layer of the second part independently contains a plasticizer in an amount ranging from 30 parts by weight to 50 parts by weight based on 100 parts by weight of polyvinyl acetal contained therein. For example, based on 100 parts by weight of polyvinyl acetal contained in each layer of the second part, the amount of plasticizer contained in each layer of the second part can be 30 parts by weight, 31 parts by weight, 32 parts by weight, 33 parts by weight, 34 parts by weight, 35 parts by weight, 36 parts by weight, 37 parts by weight, 38 parts by weight, 39 parts by weight, 40 parts by weight, 41 parts by weight, 42 parts by weight, 43 parts by weight, 44 parts by weight, 45 parts by weight, 46 parts by weight, 47 parts by weight, 48 parts by weight, 49 parts by weight, or 50 parts by weight, or within a range between any two values described herein. In a preferred embodiment of the invention, each layer of the second portion independently contains a plasticizer in an amount ranging from 38 parts by weight to 44 parts by weight based on 100 parts by weight of the polyvinyl acetal contained therein.
[0057] 1.3.3. Other common additives
[0058] Conventional additives include any material that can appropriately improve the processability of polymer film during the production of polymer film, or can impart specific functions to polymer film. The specific functions include, but are not limited to, one or more of heat insulation function, reflection function, anti-reflection function, refraction function, anti-refraction function, light division function, and light control function.
[0059] Examples of common additives include, but are not limited to, dyes, pigments, stabilizers, antioxidants, flame retardants, infrared absorbers, infrared blocking agents, ultraviolet absorbers, ultraviolet stabilizers, lubricants, dispersants, surfactants, chelating agents, coupling agents, binders, and adhesion control agents. For example, the polymer film may contain dyes or pigments to form a colored polymer film. The polymer film may also contain ultraviolet absorbers or infrared absorbers to form a polymer film having ultraviolet protection or infrared protection functions. The above additives may be used alone or in combination of two or more. The above additives may also be added to one or more layers of the first part of the polymer film, one or more layers of the second part of the polymer film, or one or more layers of the first and second parts of the polymer film.
[0060] 1.4. Other properties of polymer films
[0061] In a preferred embodiment of the present invention, based on the total thickness of the first and second parts, the thickness ratio of the first part (i.e., the thickness ratio of the first part to the total thickness of the first and second parts) is 0.05 to 0.4, e.g., 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, or 0.4, or in a range between any two values described herein. Based on the total thickness of the first and second parts, the thickness ratio of the second part (i.e., the thickness ratio of the second part to the total thickness of the first and second parts) is 0.6 to 0.95, e.g., 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, or 0.95, or in a range between any two values described herein.
[0062] As a condition that the polymer film satisfies a predetermined melt index and the sum of the product of the melt index and the thickness ratio, the total thickness of the polymer film of the present invention, the thickness of each layer of the first part, and the thickness of each layer of the second part can be adjusted as necessary. Generally, the total thickness of the polymer film of the present invention can be 0.1mm to 2.5mm, for example, 0.1mm, 0.15mm, 0.2mm, 0.25mm, 0.3mm, 0.35mm, 0.4mm, 0.45mm, 0.5mm, 0.55mm, 0.6mm, 0.65mm, 0.7mm, 0.75mm, 0.8mm, 0.85mm, 0.9mm, 0.95mm, 1.0mm, 1.05mm, 1.1mm, 1.15mm, 1.2mm, 1.25mm The thickness of the polymer film may be 1.3 mm, 1.35 mm, 1.4 mm, 1.45 mm, 1.5 mm, 1.55 mm, 1.6 mm, 1.65 mm, 1.7 mm, 1.75 mm, 1.8 mm, 1.85 mm, 1.9 mm, 1.95 mm, 2.0 mm, 2.05 mm, 2.1 mm, 2.15 mm, 2.2 mm, 2.25 mm, 2.3 mm, 2.35 mm, 2.4 mm, 2.45 mm, or 2.5 mm, or within a range between any two values listed herein. In the accompanying examples, the polymer film has a thickness of 0.76 mm to 0.85 mm.
[0063] In some embodiments of the invention, the thickness of each layer of the first portion can independently be from 50 μm to 250 μm, e.g., 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, or 250 μm, or within a range between any two values described herein.
[0064] In some embodiments of the invention, the thickness of each layer of the second portion can independently be from 250 μm to 450 μm, e.g., 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, 300 μm, 310 μm, 320 μm, 330 μm, 340 μm, 350 μm, 360 μm, 370 μm, 380 μm, 390 μm, 400 μm, 410 μm, 420 μm, 430 μm, 440 μm, or 450 μm, or within a range between any two values described herein.
[0065] 1.5. Polymer film production
[0066] The method for producing the polymer film of the present invention is not particularly limited. For example, the polymer film of the present invention may be produced by mixing polyvinyl acetal and optional components (e.g., plasticizer), dry stirring and kneading to obtain a polymer composition, using the polymer composition to obtain a polymer film by a conventional film forming method, and performing a mechanical embossing process on the surface of the polymer film. Examples of conventional film forming methods include, but are not limited to, a calendar method, a casting method, an extrusion stretching method, a direct extrusion method, an extrusion blow method, etc.
[0067] In some embodiments of the present invention, the polymer film is produced as follows, but the present invention is not limited thereto: a first polymer film composition for producing each layer of the first part and a second polymer film composition for producing each layer of the second part are prepared, and the first polymer film composition and the second polymer film composition are put into a co-extruder to form the polymer film of the present invention by co-extrusion.
[0068] The first polymer film composition and the second polymer film composition can be prepared independently as follows, but the present invention is not limited thereto: preheat the selected polyvinyl acetal resin in an oven, dry-stir the preheated polyvinyl acetal and plasticizer to obtain a dry-stirred mixture, and then knead the dry-stirred mixture using a twin-screw kneader to obtain the desired first polymer film composition or second polymer film composition.
[0069] Without being limited by any theory, it is believed that the melt index of a polymer film can be adjusted by controlling the amount of functional groups of the polymer, the amount of plasticizer in the polymer film, and the uniformity of absorption of the plasticizer in the polymer. The uniformity of absorption of the plasticizer in the polymer can be adjusted by controlling the preheating temperature, dry stirring temperature, dry stirring time, kneading temperature, and kneading time during the production of the polymer film. In general, preheating expands the pores between the polymer materials to slightly increase the fluidity of the resin, making it easier to mix with the plasticizer thereafter. Increasing the dry stirring temperature promotes the expansion of the pores and promotes the absorption of the plasticizer. Increasing the dry stirring time results in a more uniform mixture of the resin and the plasticizer. Increasing the kneading temperature improves the fluidity of the plasticizer, which in turn improves the compatibility of the resin and the plasticizer. Increasing the kneading time can result in a more uniform mixture of the resin and the plasticizer. In addition, the amount of functional groups of the polymer also affects the uniformity of absorption of the plasticizer into the polymer. From the above, in the attached examples, in addition to adjusting the compositions of the first polymer film composition and the second polymer film composition, a polymer film having the melt index characteristics required by the present invention is also provided under the conditions of a preheating temperature of 30°C to 45°C, a dry stirring temperature of 30°C to 45°C, a dry stirring time of 2 minutes to 3 minutes, a kneading temperature of 180°C to 210°C, and a kneading time of 8 minutes to 12 minutes.
[0070] The uneven structure is formed on the surface of the coextruded polymer film by preheating and mechanical embossing to promote degassing. Mechanical embossing refers to a process of forming a texture on the surface of the polymer film using a roller. Examples of mechanical embossing methods include, but are not limited to, the embossing roller method or the calendar roller method. The embossing roller method is preferred. The type of texture formed by mechanical embossing is not particularly limited, and includes diamond-shaped texture, linear texture, sawtooth texture, square texture, tapered texture, circular texture, subcircle texture, irregular texture, etc. The above texture types may be used alone or in combination of two or more types. The conditions of preheating and mechanical embossing can be appropriately adjusted according to the composition of the polymer film.
[0071] 2.Laminated glass
[0072] The polymer film of the present invention can be used to manufacture laminated glass. The present invention therefore also provides a laminated glass comprising, in order, a first glass sheet, an intermediate film and a second glass sheet, the intermediate film being the polymer film described above.
[0073] The first glass sheet and the second glass sheet may be the same or different from each other. The first glass sheet and the second glass sheet may be any glass sheet for conventional laminated glass production, independently of each other. Examples of conventional glass sheets for laminated glass production include float glass sheets, tempered glass sheets, wired glass sheets, plain plate glass sheets, etc., but the present invention is not limited thereto. In the attached examples, float glass sheets are used as the first glass sheet and the second glass sheet.
[0074] The laminated glass of the present invention can be produced by any method for producing laminated glass known in the art. In general, the method for producing laminated glass can be roughly divided into a pre-pressing process and an autoclave pressing process. The pre-pressing process is as follows. First, a polymer film is sandwiched between two glass sheets to obtain a laminate. Next, the conveying speed of the belt conveyor of the roller press is set to 2 m / min to 8 m / min, the oven temperature is set to 160°C to 190°C, and the roller pressure is set to 3 kg / cm. 2 ~10kg / cm 2 The laminate is placed on a belt conveyor and passes through an oven and rollers with the distance between the rollers set to 4.5 mm to 6.5 mm in sequence. The laminate pressed by the rollers is then cooled to room temperature, completing the prepress. Next, the prepressed laminate is placed in an autoclave to perform the autoclave pressing process. The autoclave pressing process is a process in which the prepressed laminate is hot pressed under high pressure and high temperature conditions for 100 to 150 minutes to obtain laminated glass. Generally, the high pressure and high temperature conditions refer to a pressure in the range of 10 bar to 15 bar and a temperature in the range of 100°C to 150°C.
[0075] 3. Working Example
[0076] Test Method
[0077] The present invention will be further described below with reference to the following embodiments. The test device and test method are as follows.
[0078] [Measurement of acetalization degree, acetylation degree and hydroxyl group content of polyvinyl acetal]
[0079] The degree of acetalization, the degree of acetylation and the hydroxyl group content of polyvinyl acetal are measured in accordance with JIS K6728:1977.
[0080] [Measurement of molecular weight distribution of polyvinyl acetal]
[0081] The molecular weight distribution of polyvinyl acetal is measured by gel permeation chromatography (GPC). GPC analysis is performed by dissolving polyvinyl acetal in tetrahydrofuran (THF) under the following conditions. The molecular weight (Mn) of polyvinyl acetal is calculated based on the ratio equivalent to the area of standard polystyrene (Water PS STD). Equipment: Waters 1515 PUMP system Detector: Waters 2414 RI Elution conditions: 1.0mL / min, THF Column: Waters Styragel HR5 THF, Waters Styragel HR4 THF, Waters Styragel HR3 THF, Waters Styragel HR1 THF
[0082] [Melt index measurement]
[0083] The melt index of the polymer film is measured according to ASTM D1238 using a melt index tester (model: D4002HV, available from Dynisco). The calculation of the outflow weight is performed according to the manual operation method (method A). The measurement conditions are 190°C, load 2.16 kg, and the polymer film sample weight is 6 g. The detailed measurement steps are as follows. First, the polymer film sample is placed in a constant temperature and humidity chamber at 23°C and 25% relative humidity for 2 hours. Then, the melt index tester is switched on to heat it to 190°C, and the sample is added and packed into a cylindrical barrel. A standard load is applied to the sample in the cylindrical barrel via a piston and a weight (total weight 2.16 kg), and the sample that flows out within 120 seconds is excluded from the calculation. The formal test starts after 120 seconds. The outflow amount of the sample is weighed three times every 200 seconds. The melt index is calculated by the following formula. The unit of melt index is g / 10 min. MI = (total weight of outflow (unit: g)) / (outflow collection time (10 min))
[0084] [Evaluation of continuous layer structure]
[0085] The polymer film is observed using an optical microscope (model: BX51, manufactured by Olympus) to confirm whether the structure of each layer is continuous. The polymer film is cut into a sample of 100 cm x 5 cm (100 cm horizontal length, 5 cm vertical length). Using a clamping jig, the two short sides of the sample are clamped so that the long side of the polymer film (i.e., the cut surface) faces the objective lens. The optical microscope is set as follows, with the objective lens magnification of 5x. The evaluation criteria are as follows. If the structure of each layer of the polymer film is continuous and no discontinuity is observed, the uniformity of the structure is good, and the result is recorded as "○". If discontinuity is observed in any layer of the polymer film, the uniformity of the structure is poor, and the result is recorded as "×".
[0086] [Layer thickness evaluation]
[0087] The thickness of each layer in the first part and each layer in the second part of the polymer film is measured using an optical microscope (model: BX51, manufactured by Olympus), and the thickness is calculated using the built-in software of the optical microscope (Motic Image Plus 2.0). The polymer film is cut into a sample of 100 cm x 5 cm. Here, 100 cm is the horizontal length and 5 cm is the vertical length. Using a clamping jig, the two short sides of the sample are clamped so that the long side of the polymer film (i.e., the cut surface) faces the objective lens. The optical microscope is set as follows, with the objective lens magnification of 5 times. The measurement method of each layer in the first part and each layer in the second part is as follows. The thickness of the layer is measured at positions 1 cm, 25 cm, 50 cm, 75 cm, and 100 cm from the left boundary, respectively, to obtain five thickness values. The thickness of each layer in the first part and each layer in the second part is calculated by averaging the five values.
[0088] [Loss factor evaluation]
[0089] The loss factor of the laminated glass is evaluated according to ISO 16940:2008, Measurement of Mechanical Impedance (MIM). The sample is prepared as follows. First, a polymer film with a length of 300 mm and a width of 25 mm is sandwiched between two sheets of float glass (length: 300 mm, width: 25 mm, thickness: 2 mm) to obtain a laminate. This laminate is subjected to a pre-pressing process and an autoclave pressing process to obtain a laminated glass. The pre-pressing process and the autoclave pressing process are as described above. Next, this laminated glass is placed in a thermo-hygrostat at 23°C and a relative humidity of 55% for 2 hours. After that, the loss factor test is performed as follows. First, the center of the laminated glass is fixed to a vibration exciter, and the laminated glass is vibrated at an ambient temperature of 20°C. Next, the force and frequency of vibrating the laminated glass are measured using an impedance head, and the obtained value is converted into a damping loss factor by an analysis system. The calculation is performed according to the first vibration mode using the half-power method. If the attenuation loss coefficient of the laminated glass at 20°C is 0.25 or more, good sound insulation performance is obtained.
[0090] [Dropping ball test]
[0091] The ball drop test is performed at 23°C in accordance with the penetration resistance test described in JIS R 3212:1998 (hereinafter referred to as "Standard 3212"). First, five sheets of 30 cm x 30 cm laminated glass are prepared as test samples. Next, the test sample is placed on a steel support frame conforming to Standard 3212, and a steel ball weighing 2260 g and having a diameter of 82 mm is placed 5 m above the test sample, and the steel ball is allowed to freely fall onto the test sample to confirm whether the steel ball penetrates the test sample. The test is performed five times. If the steel ball does not penetrate the test sample all five times, the ball drop test is considered to be passed, and the result is recorded as "○". If the steel ball penetrates the test sample in any of the five tests, the ball drop test is considered to be failed, and the result is recorded as "X".
[0092] [Snowflake defect testing]
[0093] As used herein, a "snowflake defect" refers to a defect that looks like a snowflake and occurs between a first portion and a second portion of a polymer film. Snowflake defects are typically formed during the manufacture of laminated glass and adversely affect the optical performance of the laminated glass. The test for snowflake defects is as follows:
[0094] Prepare a 15cm x 15cm piece of laminated glass as a test sample. Place this test sample in an oven at 120°C for 2 hours. Remove from the oven and observe the appearance of the test sample (laminated glass) with the naked eye. If no snowflake defects are observed, the snowflake defect test is passed and the result is recorded as "○". If snowflake defects are observed, the snowflake defect test is failed and the result is recorded as "×".
[0095] [Light transmittance measurement]
[0096] The light transmittance of laminated glass is measured according to ASTM D1003. First, two flat glass sheets, each 6 cm long, 6 cm wide, and 3 mm thick, are washed with water and dried. Next, a polymer film is sandwiched between the two glass sheets to obtain a laminate. The laminate is then heated at 150°C and 3 kg / cm2 using a hot press machine. 2 This laminate is hot pressed for 3 minutes under the above conditions to obtain a laminated glass. The glass surface is washed with alcohol. Then, the light transmittance of the laminated glass is measured using a haze meter (model: NDH2000 haze meter, manufactured by Nippon Denshoku Industries Co., Ltd.). Generally, the light transmittance of a suitable laminated glass is considered to be 87.5% or more.
[0097] 3.2. Polymer film production and physical property measurement
[0098] 3.2.1. First Part of Polymer Film
[0099] 100 parts by weight of poly(vinyl butyral) (PVB, manufactured by Chang Chun Petrochemical Co., Ltd.) was preheated in an oven at 30°C to 45°C for 1 minute. Next, the preheated PVB and the plasticizer were dry-stirred at a first dry-stirring temperature and a first dry-stirring time to obtain a first dry-stirring mixture. Then, the first dry-stirring mixture was kneaded at a first kneading temperature and a first kneading time using a twin-screw kneader to obtain first polymer film compositions of Examples 1 to 11 and Comparative Examples 1 to 11, respectively. The blending amount of the plasticizer is shown in Tables 1-1 and 2-1, and the first dry-stirring temperature, the first dry-stirring time, the first kneading temperature, and the first kneading time are shown in Tables 1-2 and 2-2. The physical properties of the PVB (Mn, acetalization degree, acetylation degree, hydroxyl group content) were measured according to the above-mentioned test methods, and the results are shown in Tables 1-1 and 2-1. The unit for the degree of acetalization, the degree of acetylation, and the hydroxyl group content is all mol %.
[0100] The first polymer film compositions of Examples 1 to 11 and Comparative Examples 1 to 11 were each placed in an extruder to obtain a monolayer polymer film (hereinafter referred to as "first monolayer polymer film"). The melt index of each of the first monolayer polymer films was measured according to the above-mentioned test method, and the results are shown in Tables 1-6 and 2-6, i.e., "Melt Index of Layer I". Each of the first polymer film compositions was used as the material of each layer of the first part of the polymer film of Examples 1 to 11 and Comparative Examples 1 to 11 described later, and the melt index of each of the first monolayer polymer films represents the melt index of each layer of the first part.
[0101] 3.2.2. Second Part of Polymer Film
[0102] 100 parts by weight of poly(vinyl butyral) (PVB, manufactured by Chang Chun Petrochemical Co., Ltd.) was preheated in an oven at 30°C to 45°C for 1 minute. Next, the preheated PVB and the plasticizer were dry-stirred at a second dry-stirring temperature and a second dry-stirring time to obtain a second dry-stirring mixture. Then, the second dry-stirring mixture was kneaded at a second kneading temperature and a second kneading time using a twin-screw kneader to obtain second polymer film compositions of Examples 1 to 11 and Comparative Examples 1 to 11, respectively. The blending amount of the plasticizer is shown in Tables 1-3 and 2-3, and the second dry-stirring temperature, the second dry-stirring time, the second kneading temperature, and the second kneading time are shown in Tables 1-4 and 2-4. The physical properties of the PVB (Mn, acetalization degree, acetylation degree, hydroxyl group content) were measured according to the above-mentioned test methods, and the results are shown in Tables 1-3 and 2-3. The unit for the degree of acetalization, the degree of acetylation, and the hydroxyl group content is all mol %.
[0103] The second polymer film compositions of Examples 1 to 11 and Comparative Examples 1 to 11 were each placed in an extruder to obtain a monolayer polymer film (hereinafter referred to as "second monolayer polymer film"). The melt index of each of the second monolayer polymer films was measured according to the above-mentioned test method, and the results are shown in Tables 1-7 and 2-7, i.e., "Melt Index of Layer II". Each second polymer film composition was used as the material of each layer of the second part of the polymer film of Examples 1 to 11 and Comparative Examples 1 to 11 described later, and the melt index of each second monolayer polymer film represents the melt index of each layer of the second part.
[0104] 3.2.3. Polymer film production
[0105] The first polymer film composition of Examples 1-11 and Comparative Examples 1-11, and the second polymer film composition of Examples 1-11 and Comparative Examples 1-11 were each placed in a co-extruder, and a polymer film was formed by co-extrusion. The total thickness of the polymer film was 0.8 mm, and the configuration of the polymer film is as shown in Tables 1-5 and 2-5, where "I layer" represents the layer of the first part of the polymer film formed from the first polymer film composition, and "II layer" represents the layer of the second part of the polymer film formed from the second polymer film composition. The total thickness of the I layer constituting the first part of the polymer film and the thickness ratio of the total thickness of the I layer to the total thickness of the first part and the second part are shown in Tables 1-6 and 2-6. In addition, the total thickness of the II layer constituting the second part of the polymer film and the thickness ratio of the total thickness of the II layer to the total thickness of the first part and the second part are shown in Tables 1-7 and 2-7. In an embodiment in which the polymer film includes two or more I or II layers, each of the I layers has the same thickness, and each of the II layers has the same thickness. Therefore, the thickness ratio of each layer can be calculated from the total thickness ratio listed in the table, and the product and sum of the products of the melt index and thickness ratio of each layer can be calculated accordingly.
[0106] Thereafter, the two surfaces of the polymer film were preheated and mechanically embossed to form a texture, thereby obtaining the polymer films of Examples 1-11 and Comparative Examples 1-11.
[0107] [Table 1-1]
[0108] [Table 1-2]
[0109] [Table 1-3]
[0110] [Table 1-4]
[0111]
Table 1-5
[0112]
Table 1-6
[0113]
Table 1-7
[0114]
Table 2-1
[0115]
Table 2-2
[0116]
Table 2-3
[0117]
Table 2-4
[0118]
Table 2-5
[0119]
Table 2-6
[0120]
Table 2-7
[0121] 3.3. Manufacturing of laminated glass and evaluation of its physical properties
[0122] Laminated glass was produced using each of the polymer films of Examples 1 to 11 and Comparative Examples 1 to 11. First, the polymer film was cut to 300 mm x 300 mm. Next, for each polymer film, two clean, transparent float glass sheets (length: 300 mm, width: 300 mm, thickness: 2 mm) were prepared. The cut polymer films of Examples 1 to 11 and Comparative Examples 1 to 11 were each sandwiched between two transparent float glass sheets to obtain a laminate. This laminate was pre-pressed by vacuum drawing using nip rollers. Pre-pressing with nip rollers was performed as follows. The conveying speed of the belt conveyor of the roller press was 4.5 m / min, the oven temperature was 180°C, and the roller pressure was 3 kg / cm. 2 The laminate was placed on a belt conveyor and passed through an oven and rollers in that order. The distance between the rollers was 5 mm. The pre-pressed laminate was then placed in an autoclave and hot pressed at a pressure of 13 bar and a temperature of 135°C for 120 minutes, and then cooled to room temperature to obtain a laminated glass.
[0123] The polymer films and laminated glasses of Examples 1 to 11 and Comparative Examples 1 to 11 were subjected to evaluation of the continuous layer structure, evaluation of the loss factor, ball drop test, snowflake defect test, and measurement of light transmittance according to the above-mentioned test methods. The results are shown in Tables 3-1 and 3-2.
[0124] [Table 3-1]
[0125] [Table 3-2]
[0126] As shown in Table 3-1, Examples 1 to 11 show that the polymer film of the present invention has a continuous layer structure and good structural uniformity. The laminated glass manufactured from the polymer film of the present invention has a loss factor of more than 0.25, i.e., good sound insulation effect. Furthermore, the laminated glass manufactured from the polymer film of the present invention can pass the falling ball test and the snowflake defect test, and has a suitable light transmittance (i.e., 87.5% or more).
[0127] In contrast, as shown in Table 3-2, laminated glass made from a polymer film not according to the present invention cannot simultaneously have excellent sound insulation, excellent optical properties, and excellent safety. In particular, according to Comparative Examples 1 and 11, when the melt index of each layer of the first portion and the sum of the products of the melt index and the thickness ratio of each layer of the first portion are lower than a predetermined range, even if the melt index of each layer of the second portion and the sum of the products of the melt index and the thickness ratio of each layer of the second portion are within a predetermined range, the structural uniformity of the polymer film is poor, and the sound insulation effect of the manufactured laminated glass is poor (loss factor is less than 0.25). According to Comparative Example 2, when the melt index of each layer of the first part and the sum of the products of the melt index and the thickness ratio of each layer of the first part are higher than the predetermined range, even if the melt index of each layer of the second part and the sum of the products of the melt index and the thickness ratio of each layer of the second part are within the predetermined range, the laminated glass produced does not have excellent safety (fails the drop ball test) and has poor optical properties (fails the snowflake defect test, light transmittance is less than 87.5%). According to Comparative Examples 3 and 4, when the sum of the products of the melt index and the thickness ratio of each layer of the first part is outside the predetermined range, even if the melt index of each layer of the second part and the sum of the products of the melt index and the thickness ratio of each layer of the second part are within the predetermined range and the melt index of each layer of the first part is within the predetermined range, the laminated glass produced has low sound insulation effect (loss factor is less than 0.25) or poor optical properties (light transmittance is less than 87.5%). According to Comparative Example 5, when the melt index of each layer of the second part and the sum of the products of the melt index and the thickness ratio of each layer of the second part are higher than the specified range, even if the sum of the products of the melt index and the thickness ratio of each layer of the first part is within the specified range, the safety of the manufactured laminated glass is inferior (failed the ball drop test) and the optical properties are also inferior (failed the snowflake defect test, light transmittance 87.5%).According to Comparative Example 6, when the melt index of each layer of the second part and the sum of the product of the melt index and the thickness ratio of each layer of the second part are lower than a predetermined range, the optical properties of the manufactured laminated glass are poor (failed the snowflake defect test) even if the melt index of each layer of the first part and the sum of the product of the melt index and the thickness ratio of each layer of the first part are within a predetermined range. According to Comparative Example 7, when the melt index of each layer of the first part and the second part and the sum of the product of the melt index and the thickness ratio of each layer of the first part and the second part are higher than the predetermined range, the manufactured laminated glass is not excellent in safety (failed the ball drop test) and has poor optical properties (failed the snowflake defect test, light transmittance less than 87.5%). According to Comparative Example 8, when the melt index of each layer of the first and second parts and the sum of the products of the melt index and the thickness ratio of each layer of the first and second parts are lower than a predetermined range, the uniformity of the polymer film structure is poor, and the laminated glass produced has a poor sound insulation effect (loss factor less than 0.25). According to Comparative Example 9, when the sum of the products of the melt index and the thickness ratio of each layer of the first part, the melt index of each layer of the second part and the sum of the products of the melt index and the thickness ratio of each layer of the second part are out of a predetermined range, the laminated glass produced has poor safety (failed the ball drop test) and poor optical properties (failed the snowflake defect test, light transmittance less than 87.5%). According to Comparative Example 10, when the melt index of each layer of the first portion and the sum of the product of the melt index and the thickness ratio of each layer of the first portion were higher than a specified range, the safety of the manufactured laminated glass was poor. On the other hand, when the melt index of each layer of the second portion and the sum of the product of the melt index and the thickness ratio of each layer of the second portion were lower than a specified range, the manufactured laminated glass did not have excellent safety (failed the ball drop test) and also had poor optical properties (failed the snowflake defect test, light transmittance 87.5%).
[0128] The above examples are used to explain the principle and effectiveness of the present invention and to demonstrate its inventive features, but are not used to limit the scope of the present invention. Those skilled in the art can proceed with various modifications and substitutions based on the disclosure and suggestions of the present invention described. Therefore, the protection scope of the present invention is as defined in the appended claims.
[0129] (Additional Note) (Appendix 1) A first portion and a second portion laminated to the first portion, the first portion and the second portion being independently a polymer film composed of one or more layers, each layer of the first portion independently has a melt index in the range of 3.5 g / 10 min to 10.0 g / 10 min, and each layer of the second portion independently has a melt index less than 3.5 g / 10 min; each layer of the first portion independently has a thickness ratio of its thickness to a total thickness of the first portion and the second portion, and a product of its melt index and the thickness ratio, wherein the sum of the products of each layer of the first portion is in the range of 0.39 g / 10 min to 2.50 g / 10 min; Each layer of the second portion independently has a thickness ratio of its thickness to a total thickness of the first portion and the second portion, and a product of its melt index and the thickness ratio, with the sum of the products of each layer of the second portion being in the range of 1.10 g / 10 min to 2.95 g / 10 min; A polymer film characterized in that
[0130] (Appendix 2) The melt index of each layer of the second portion is independently 1.5 g / 10 min to 3.3 g / 10 min; 2. The polymer film according to claim 1 .
[0131] (Appendix 3) The melt index of each layer of the first portion and the melt index of each layer of the second portion are measured according to ASTM D1238 at 190° C. and a load of 2.16 kg; 2. The polymer film according to claim 1 .
[0132] (Appendix 4) each layer of the first portion and each layer of the second portion each independently comprises polyvinyl acetal; 4. The polymer film according to claim 1,
[0133] (Appendix 5) each layer of the first portion and each layer of the second portion each independently comprises poly(vinyl butyral); 5. The polymer film according to claim 4,
[0134] (Appendix 6) each layer of the first portion independently contains polyvinyl acetal having a degree of acetalization of 56 mol% to 74 mol%, a degree of acetylation of 5 mol% to 15 mol%, and a hydroxyl group content of 20 mol% to 30 mol%; 5. The polymer film according to claim 4,
[0135] (Appendix 7) each layer of the second portion independently contains polyvinyl acetal having an acetalization degree of 60 mol% to 75 mol%, an acetylation degree of 0.1 mol% to 5 mol%, and a hydroxyl group content of 20 mol% to 35 mol%; 5. The polymer film according to claim 4,
[0136] (Appendix 8) The number average molecular weight (Mn) of the polyvinyl acetal contained in each layer of the first portion is independently 100,000 to 240,000. 5. The polymer film according to claim 4,
[0137] (Appendix 9) 5. The polymer film according to claim 4, wherein the polyvinyl acetal contained in each layer of the second portion independently has a number average molecular weight (Mn) of 90,000 to 120,000.
[0138] (Appendix 10) each layer of the first portion and each layer of the second portion each independently further comprises a plasticizer; 5. The polymer film according to claim 4,
[0139] (Appendix 11) Each layer of the first portion independently contains a plasticizer in an amount ranging from 55 parts by weight to 85 parts by weight based on 100 parts by weight of the polyvinyl acetal contained therein, and each layer of the second portion independently contains a plasticizer in an amount ranging from 30 parts by weight to 50 parts by weight based on 100 parts by weight of the polyvinyl acetal contained therein. 11. The polymer film according to claim 10,
[0140] (Appendix 12) one or more layers of the first portion constitute first subportions and one or more layers of the second portion constitute second subportions, the first subportions and the second subportions are arranged in an alternating manner, the number of the first subportions is M, the number of the second subportions is N, and M and N are independently positive integers; 4. The polymer film according to claim 1,
[0141] (Appendix 13) N is M+1, 13. The polymer film according to claim 12,
[0142] (Appendix 14) A laminated glass comprising, in order, a first glass sheet, an intermediate film, and a second glass sheet, The intermediate film is a polymer film according to any one of claims 1 to 3. The laminated glass is characterized by the above-mentioned.
Claims
1. A first portion and a second portion laminated to the first portion, the first portion and the second portion being independently a polymer film composed of one or more layers, each layer of the first portion independently has a melt index in the range of 3.5 g / 10 min to 10.0 g / 10 min, and each layer of the second portion independently has a melt index less than 3.5 g / 10 min; each layer of the first portion independently has a thickness ratio of its thickness to a total thickness of the first portion and the second portion, and a product of its melt index and said thickness ratio, wherein the sum of said products for each layer of the first portion is in the range of 0.39 g / 10 min to 2.50 g / 10 min; each layer of the second portion independently has a thickness ratio of its thickness to a total thickness of the first portion and the second portion, and a product of its melt index and the thickness ratio, wherein the sum of the products of each layer of the second portion is in the range of 1.10 g / 10 min to 2.95 g / 10 min; A polymer film characterized in that
2. the melt index of each layer of the second portion is independently from 1.5 g / 10 min to 3.3 g / 10 min; 2. The polymer film of claim 1.
3. The melt index of each layer of the first portion and the melt index of each layer of the second portion are measured according to ASTM D1238 at 190° C. and a load of 2.16 kg; 2. The polymer film of claim 1.
4. each layer of the first portion and each layer of the second portion each independently comprises polyvinyl acetal; 4. The polymer film according to claim 1 .
5. each layer of the first portion and each layer of the second portion each independently comprises poly(vinyl butyral); 5. The polymer film according to claim 4.
6. each layer of the first portion independently comprises a polyvinyl acetal having a degree of acetalization of 56 mol % to 74 mol %, a degree of acetylation of 5 mol % to 15 mol %, and a hydroxyl group content of 20 mol % to 30 mol %; 5. The polymer film according to claim 4.
7. each layer of the second portion independently comprises a polyvinyl acetal having a degree of acetalization of 60 mol % to 75 mol %, a degree of acetylation of 0.1 mol % to 5 mol %, and a hydroxyl group content of 20 mol % to 35 mol %; 5. The polymer film according to claim 4.
8. The number average molecular weight (Mn) of the polyvinyl acetal contained in each layer of the first portion is independently 100,000 to 240,000.
5. The polymer film according to claim 4.
9. The polymer film according to claim 4, wherein the number average molecular weight (Mn) of the polyvinyl acetal contained in each layer of the second portion is independently 90,000 to 120,000.
10. each layer of the first portion and each layer of the second portion each independently further comprises a plasticizer; 5. The polymer film according to claim 4.
11. Each layer of the first portion independently contains a plasticizer in an amount ranging from 55 parts by weight to 85 parts by weight based on 100 parts by weight of polyvinyl acetal contained therein, and each layer of the second portion independently contains a plasticizer in an amount ranging from 30 parts by weight to 50 parts by weight based on 100 parts by weight of polyvinyl acetal contained therein. The polymer film of claim 10.
12. one or more layers of the first portion constitute first subportions, one or more layers of the second portion constitute second subportions, the first subportions and the second subportions are arranged in an alternating manner, the number of the first subportions is M, the number of the second subportions is N, and M and N are independently positive integers; 4. The polymer film according to claim 1 .
13. N is M+1; 13. The polymer film of claim 12.
14. A laminated glass comprising, in order, a first glass sheet, an intermediate film, and a second glass sheet, The intermediate film is a polymer film according to any one of claims 1 to 3. The laminated glass is characterized by the above-mentioned.
Citation Information
Patent Citations
Interlayer for laminated glasses, and laminated glass
JP2004083360A
Interlayer for laminated glass and laminated glass
JP2007331959A
Polymer film
JP2023086680A
Polymer film
JP2023086683A
Interlayer for laminated glass, and laminated glass
WO2011081190A1